Socialization of the penak application (master and child assistance) regarding the prevention of early marriage in the dlingo community, bantul, yogyakarta - Enny Fitriahadi; Islamiyatur Rokhmah; Danur Wijayanto (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Early marriage is a formal or informal marriage under the age of 18. This can lead to lifelong loss and deprivation for minors especially girls. The approach through parent and child assistance is inseparable from the monitoring of local community cadres or leaders. Cases of early marriage in Dlingo District, Bantul Regency, have increased in recent years. One that encourages early marriage includes social and economic issues, child association, restrictions on personal freedom and lack of education due to online learning during the Covid-19 pandemic. Partners in Dlingo Bantul have implemented penak but it is still manual, with the diffusion of science and technology in the field of penak application model technology which includes reproductive health knowledge features that can create a sakinah mawadah warohmah family, the welfare of young families and the prevention of future generations from stunting. Through the socialization of the penak application about preventing early marriage, the community, especially teenagers and parents, can apply and use the website to prevent early marriage so that the community's health status can increase and can prevent stunting, especially the people in Dlingo, Bantul Regency.